Fdi Versus Exports in a General Equilibrium Ricardian Model - Noguera-Santaella, J (2011)
In a two-country general equilibrium Ricardian model, we propose a model in which countries compete in the same sectors via exports or foreign direct investment (FDI). Factor endowments are important in that they affect relative wages and the range of goods countries produce. Effects of factor endowments on FDI depend on the interaction of FDI and trade barriers. Transportation costs do favour FDI at the expense of exports, but reduce trade and investment. Finally, in contrast to the new trade theory, across industries, it is the relatively less productive firms that engage in FDI while the relatively more productive firms export. © 2011 The Economic Society of Australia.